Andragogical and pedagogical methods for curriculum and program development - Wang, Victor C. X.; Bryan, Valerie C. (Hershey, PA Information Science Reference, 2014)
"This book offers an in-depth description of key terms and concepts related to curriculum and program development for both faculty and students, as well as program designers, instructional program developers, trainers, and librarians"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Adult learning; Adult education -- Curricula